The Influence of Current Ratio, Return on Investment, Asset Growth, and Debt to Equity Ratio on Dividend Payout Ratio in Basic Food Retailing, Food and Beverage Companies Listed on the Indonesian Stock Exchange in 2021-2023 - Niken Apriliana; Andar Febyansyah (Neo Journal of economy and social humanities, 2025)
This research aims to test the influence of the Current ratio, Return On Investment, Asset Growth, and Debt To Equity Ratio on the Dividend Payout Ratio. This research uses secondary data with a type of causal research. The population used in this research is food and beverage companies listed on the Indonesian Stock Exchange (BEI). The observation period in this research starts from 2021-2023, using financial report data from 15 companies in the food and beverage sector for 3 years. The sampling technique used was purposive sampling. The research results show that, simultaneously the Current ratio, Return On Investment, Asset Growth, and Debt To Equity Ratio have a significant effect on the Dividend Payout Ratio. Partially, the Current Ratio has a significant positive effect on the Dividend Payout Ratio. Return on Investment and Asset Growth have a negative and insignificant effect on the Dividend Payout Ratio. Meanwhile, the Debt to Equity Ratio has a positive and insignificant effect on the Dividend Payout Ratio in food and beverage companies listed on the Indonesia Stock Exchange for the 2021-2023 period.